Books and identity: the case of young-adult women bibliophiles - Cardoso, M. C.; Cardoso, M. G. M. S. (26th Recent Advances in Retailing & Services Science Conference, 2019)
The publishing industry faces several challenges, including reader engagement and reader-centric marketing. Historically, publishers have failed to paint an accurate and complete picture of the market which has often led to them being ineffective or slow to respond to the expectations of readers. With an increasing plurality of book titles, knowledge on consumer modes of thought is more important than ever to encourage reading and book-buying. As one of the most promising market segments, young-adult women bibliophiles deserve close examination. Marketing theories of symbolic and self-expressive consumption contribute to explaining various key facets of consumer behaviour. In particular, research suggests that the symbolic meanings attached to objects are linked to consumers’ sense of self, affecting their attitudes towards specific products and their shopping patterns. To date, application of such theories to the universe of books is scarce and mostly superficial. The main aim of this study was to investigate the link between books and identity (if there was any), focussing on the case of young-adult women bibliophiles. Key objectives included understanding both the meanings attributed to books and the meanings attached to the self-concept of individuals. The results of six in-depth interviews and 381 survey responses (including partial answers) provide strong empirical support for a relationship between book consumption and the development of a personal identity in the case of young-adult women book lovers, as anticipated by marketing and consumer behaviour research. Firstly, both the results of the interviews and the survey have shown that books are generally perceived as more than functional objects; they are unique symbolic forces. Evidence supporting this is found, for example, in the associations made with books (e.g., knowledge). Secondly, books are thought to carry selfconcept importance – they contribute to shaping the identity of the target population of the study. A significant share of individuals believes their interest in books says they are intelligent and openminded, for instance. In particular, the consumption of books seems to express how the individuals are (actual self), how the individuals are in a social context (social self), and also how they want to be and how they want to be perceived by others (ideal self dimensions). Amongst these four dimensions, the one that stands out the most is the actual self. Interestingly, the relationship between consumption and identity seems to be stronger when individuals perceive books as an important part of their lives. The findings are relevant for industry practitioners as they provide insights on the modes of thought and behaviour of a profitable market segment. Given the results obtained, publishers can rethink how to develop better marketing strategies to promote even higher book-buying and reading rates.